2003
DOI: 10.1038/sj.bjc.6600749
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer response to neoadjuvant chemotherapy: predictive markers and relation with outcome

Abstract: The aim of this study was to provide a better insight into breast cancer response to chemotherapy. Chemotherapy improves outcome in breast cancer patients. The effect of cytotoxic treatment cannot be predicted for individual patients. Therefore, the identification of tumour characteristics associated with tumour response and outcome is of great clinical interest. We studied 97 patients, who received anthracycline-based neoadjuvant chemotherapy. Tumour samples were taken prior to and after chemotherapy. We quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
164
4
15

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(214 citation statements)
references
References 34 publications
(36 reference statements)
22
164
4
15
Order By: Relevance
“…Bottini et al observed on multivariate analysis that clinical response, tumour size and PgR status were independent predictors for disease recurrence [15,20]. Faneyte and colleagues assessed the role of Ki67, ER, HER2, p53 and bcl2 in 97 women with breast cancer and extensive axillary node involvement and found none of these factors to be associated with DFS and OS [17]. The current findings have similarities to those we observed in patients treated with endocrine therapy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Bottini et al observed on multivariate analysis that clinical response, tumour size and PgR status were independent predictors for disease recurrence [15,20]. Faneyte and colleagues assessed the role of Ki67, ER, HER2, p53 and bcl2 in 97 women with breast cancer and extensive axillary node involvement and found none of these factors to be associated with DFS and OS [17]. The current findings have similarities to those we observed in patients treated with endocrine therapy.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, others have not found an independent relationship between post-neoadjuvant chemotherapy Ki67 and survival [14][15][16][17][18]. Three studies found ER status to be the sole independent predictor of DFS or RFS on multivariate analysis [14,16,19].…”
Section: Discussionmentioning
confidence: 98%
“…Most recently, several neoadjuvant trials suggest that ERα-tumors are more sensitive to chemotherapy than ERα+ tumors. [22][23][24][25][26][27] In addition, the world overview of adjuvant chemotherapy trials for breast cancer conducted by the Early Breast Cancer Collaborative Group supports the hypothesis that patients with ERα-breast cancer experience more benefit from adjuvant chemotherapy than patients with ERα+ disease. 28 The biological basis for the potential relationship between ERα and the effectiveness of adjuvant therapy remains uncertain, nonetheless differences in cell cycle regulation between ERα+ and ERα-tumors have, for a long time, been a central feature of most explanations that have been proffered.…”
Section: Introductionmentioning
confidence: 96%
“…The early identification of features associated with response or resistance to primary therapy are important in the development of the most effective multimodal approaches, and identifying cohorts of patients most likely to benefit from preoperative chemotherapy (PCT) [1][2][3]. Features predictive of response and outcome include steroid hormone receptor expression.…”
Section: Introductionmentioning
confidence: 99%